Could congressionally mandated incentives lead to deployment of large-scale CO2 capture, facilities for enhanced oil recovery CO2 markets and geologic CO2 storage?. (November 2020) - Edmonds, James; Nichols, Christopher; Adamantiades, Misha; Bistline, John; Huster, Jonathan; Iyer, Gokul; Johnson, Nils; Patel, Pralit; Showalter, Sharon; Victor, Nadja; Waldhoff, Stephanie; Wise, Marshall; et al.
Abstract: In passing the Bipartisan Budget Act of 2018, Congress reformed and strengthened a section of the tax code, 45Q, which provides tax credits of up to 35/ton CO2 for the capture and utilization of CO2 in qualifying applications such as enhanced oil recovery (EOR) and up to 50/ton CO2 for CO2 that is captured and permanently stored in a geologic repository. Earlier versions of the tax credit with lower credit values generated limited interest. This change to the tax code could potentially alter U.S. energy systems. This paper examines the effect of the increased 45Q credits on CO2 capture, utilization and storage (CCUS) deployment in the United States and on petroleum and power production. A range of potential outcomes is explored using five modeling tools. The paper goes on to explore the potential impact of possible modifications of the current tax credit including extension of its availability in time, the period over which 45Q tax credits can be utilized for any given asset and increases in the value of the credit as well as interactions with technology availability and carbon taxation. The paper concludes that 45Q tax credits could stimulate additional CCUS beyond that which is already underway. Highlights: Tax code section 45Q recently changed to increase credits for CO2 capture. Five models calculated 45Q's US energy and CO2 capture impacts. In 2030 models estimated increased CO2 capture from 45Q of 20–60 MtCO2 /year. 45Q increased CO2 storage and supplies to enhanced oil recovery markets. Use of the 45Q was further enhanced under a range of sensitivity experiments.